The effect of secondary hole variation on the performance of concentric cylinder top-lit up draft gasifier (TLUD) stove - Setyawan, Digdo Listyadi; Pertiwi, Arinsyah Pamudiarti; Sutjahjono, Harry; lminnafik, Nasrul (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The Bagasse is one of the fuels that can be used as biomass fuel in micro-gasification because the fuel is abundant. Bagasse is a by-product of the sugar industry which can be used as a biomass fuel for micro-gasification in Indonesia because of its abundance. Gasification is a process of converting biomass fuel into syngas fuel that occurs in the gasifier. This research was conducted to determine the effect of secondary orifice variations on the TLUD Concentric Cylinder Type gasification stove on flame length, flame temperature, fuel efflux rate and thermal efficiency with secondary orifice variations; 30, 40, and 50. The test was carried out using the water boiling test method. The results showed that the stove with 50 secondary holes produced the highest flame temperature at T2 (the temperature at the top of the TLUD stove gasifier) of 653.3 °C, the best flame duration was 14.15 minute, the highest burning rate was 0.88 gr/s. The highest thermal efficiency value was achieved by a stove with a secondary 50 exhaust hole of 67%. Based on the tests, it shows that the variation of the furnace hole affects the flame temperature, flame duration, combustion rate and thermal efficiency.